Performance Evaluation of DC Microgrid System for Residential LED Lighting Application - Awang Musa, Syarmeela Hadzwina; Abdullah, Abdul Rahim; Gan, Chin Kim; Rahim, Nor Hidayah (praiseworthyprize, 2014)
This paper proposes LED lighting applications DC microgrid system with compact LED lamps system for residential. Conventionally, the residential lighting system used the supply from the authorized energy supplier to power up all the electrical appliances at home. In Malaysia, the voltage distributed to residential area is 240V AC. However, most of electrical appliances at home are not driven in AC. Therefore, the electrical appliances that driven by DC requires AC/DC converter to operate. But the conversion process of the converter creates losses due to the switching of the device. For these reasons, the use of low voltage direct current (LVDC) distribution is attracting interest. In order to reduce the losses, the design of direct current (DC) microgrid at residential is proposed. This research aims to compare conventional residential lighting systems with proposed residential lighting system. The comparison conducted by simulation using MATLAB Simulink and experiment. The simulations are carried out to illustrate the power consumption for all cases. The experiment set up to compare the performance of all cases in term of power consumption, luminance, and voltage and current harmonic. Furthermore, this experiment consider suitable wiring design of the proposed system includes size of cable. As the results, the proposed system shows the better performance than the conventional system.